Factors impacting the company’s profitability in farming and agriculture sectors / Nur Hafizah Ahmad, Dr. Nurul Labanihuda Abdull Rahman and Abdul Hafiz Yusof - Ahmad, Nur Hafizah; Abdull Rahman, Nurul Labanihuda; Yusof, Abdul Hafiz (Universiti Teknologi MARA, Kedah, 2024)
Agriculture, forestry, and fishing have been the main sectors contributing to the Malaysian Gross Domestic Product since independent day. Eventually, the manufacturing sector has been booming since the ‘80s which boosted the Malaysian economy. Demand in the manufacturing sector creates a shift in job filling from agriculture to manufacturing. Since then, the agriculture sector faced a huge gap in worker and the sector seem to have lost popularity in gaining new employee. This study focuses on finding impacting sources to the profitability faced by farming and agriculture-listed companies in Malaysia. The timeline for this study of profitability determination in the agriculture sectors in Malaysia is from 2017 to 2021. There are 50 companies listed in Bursa Malaysia that were selected mostly based in the farming industry. The findings show that return on asset, operating margin and asset turnover have a positive relationship with profitability. Return on asset has the highest impact towards profitability followed by operating margin and asset turnover. The results will give an idea for agriculture sector management to make a decisive decision for future planning. Ultimately, it will give a guideline for the companies to avoid wastage, implement new policies, sustain productivity, and guarantee profits.